Digital Transformation of Medical Sector and Consumer Purchase Intention in New Normal Era - Oyagi, Shuka; Darma, Gede Sri (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 15 Nomor 1 Tahun 2021DO - 10.24843/MATRIK:JMBK.2021.v15.i01.p04, 2021)
New Normal era triggers a shift in consumer habit and behavior, such as increased awareness regarding the importance of health and sanitation, as well as elevated adoption of digital technology in daily activities. This study explored digital transformation aspects that impact consumer purchase intention in New Normal era, specifically in healthcare setting. An online-based quistionnaire were distributed using Google Form. A total of 225 response were retrieved and analysed using SEM technique (SmartPLS 3.2.1.). This study found that: 1) social media content quality, online customer service quality, and telehealth quality had a positive and significant impact to purchase intention; 2) telehealth quality had the most prominent impact on purchase intention, especially the support aspect; 3) website quality did not have any significant effect on consumer purchase intention. In conclusion, companies are recommended to focus on improving telehealth quality in their healthcare management system, especially by investing in reliable technical support staff to ensure assuring and pleasant experience for patients during telehealth sessions. Also, to focus more on social media content quality and online customer service quality than website refinement considering the current elevating trend on social media rahter than website.